PENAMBAHAN POTASSIUM CHLORIDE PADA BIOPLASTIK PATI SAGU DENGAN BERPENGUAT MIKROFIBRIL SELULOSA BAMBU BERBANTUKAN SONIKASI - Silviana Silviana; Puji Rahayu (Dept. of Chemical Engineering, Diponegoro University, 2017)
Sago starch based bioplastics as food packaging have drawbacks such as soft, and easily broken. This paper explains improvement of sago starch-based bioplastics reinforced with bamboo microfibrillated cellulose (MFC). Furthermore, this paper investigates effect of dispersing agent on mechanical property by using of potassium chloride (KCl) assisted by ultrasonic homogenizer. Variable used experiments were bamboo MFC concentration of 1%; 3% and 5% w/w and KCl concentration of 1%; 2% dan 3% w/v. Sago starch-based solution was prepared from 4% w/v of commercial sago starch. The mixed solution was gelatinized at temperature of 90 oC. The result showed that the 5% of bamboo MFC increased tensile strength of sago starch-based bioplastics due to purpose of bamboo MFC as reinforcement of sago starch. Further, additional of KCl reduced the dispersing time for 1 hour. Optimum result in this preliminary experiment was obtained at bamboo MFC of 5% w/w and KCl concentration of 1% w/v resulting tensile strength of 17.99 MPa.